Synaptic microenvironment and altered state of consciousness in schizophrenia: a possible link between synapse geometry and orchestrated objective reduction theory - Shahriar Ahmadpour (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract In recent decades, studies have provided convincing evidence indicating abnormalities in some aspects of consciousness in schizophrenia patients. One of the pioneering theory, orchestrated objective reduction (OR) on the mechanism of consciousness has been proposed by Hameroff and Penrose. According to OR, consciousness roots in microtubules (MTs) which act as quantum computation apparatus. OR theory attribute the consciousness generation to MTs, while the “inception” of the events begins at synaptic level where other players regulate the signal transduction and neurotransmitters bioavailability at synaptic microenvironment. Homeostasis and geometry of synaptic microenvironment are actively regulated by glial cell particularly astrocytes. Experimental and post mortem studies have documented evidence indicating the involvement of main participants of synapse such as astrocytes and extracellular matrix (ECM) in schizophrenia. This literature aims to review the role(s) of active participants of synaptic microenvironment and disturbed state of consciousness based on OR theory in schizophrenia.